Emerging Research Interest in Medical and Dental Undergraduates - Nahid Jamal; Khizer Ahmed Khan; Ahsan Shabbir (ziauddin University, 2024)
I am writing this letter to highlight the current encouraging and commendable rise in the involvement of undergraduate medical and dental students in research across Pakistan. A positive surge was detected among the medical and dental institutes reflecting increasing interest and contribution in research activities. A study in Saudi Arabia reported the relationship between rising research trends and its contributing factors, henceforth, stating that admission into residency (56.8%), interest in research (41.8%), and aid in clinical decision-making (31%) were the top three factors for research interest 1.